Alignment strategy for different types of varus knee with generic instruments: Mechanical alignment or kinematic alignment? - Haoran Lin; Qi Cheng; Guangjian Li; Jie Zhao; Qiang Wang (Journal of Orthopaedic Surgery and Research, 2023)
Abstract Objective A thorough examination of the available approaches is crucial to comprehensively understand the variance among the alignment strategies employed in total knee arthroplasty (TKA). In this study, we assessed the functional outcomes during the perioperative and postoperative periods of TKA in patients using generic instruments with varus knee to compare the mechanical alignment (MA) and kinematic alignment (KA) procedures. Methods A total of 127 patients from the First Affiliated Hospital of Wannan Medical College who had undergone unilateral TKA between November 2019 and April 2021 were included. The patients with varus knee deformity were categorized into two groups [type I (n = 64) and type IV (n = 63)] based on the modified coronal plane alignment of the knee (mCPAK) classification. The type I and IV groups were further subdivided into MA (n = 30 and n = 32) and KA subgroups (n = 34 and n = 21), respectively. The clinical information collected included sex, surgical side, age, body mass index, and perioperative data [including operation time, intraoperative blood loss, length of hospital stay, and the American Society of Anesthesiologists (ASA) classification]. All patients were monitored for 12 months post-surgery to evaluate the recovery of knee joint function. During this period, the Knee Disability and Osteoarthritis Outcome Score for Joint Replacement (KOOS JR) and the active range of motion (AROM) and visual analog scale (VAS) pain scores were compared at different time points, i.e., before the operation and 6 weeks, 6 months, and 12 months post-operation. Additionally, the patients’ subjective experiences were assessed at 6 and 12 months post-surgery using Forgotten Joint Score Knee (FJS-12 Knee), while complications were recorded throughout the monitoring period. Results No significant variances were observed in ASA classification, operation duration, blood loss volume during surgery, and hospital stay length between the patients who underwent KA TKA and those who received MA TKA (P > 0.05). During the initial 6 weeks post-operation, the KA group exhibited a significantly reduced average VAS pain score (P < 0.05), with no such differences at 6 months and 1 year after the surgery (P > 0.05). Furthermore, the KA group had significantly higher scores on the KOOS JR at 6 weeks, 6 months, and 1 year following the surgery (P < 0.05). Moreover, the AROM score of the KA group significantly improved only at 6 weeks after the surgery (P < 0.05); however, no prominent differences were found at 6 months and 1 year after the operation (P > 0.05). The KA cohort also exhibited a significant increase in FJS-12 Knee at 1 year following the operation (P < 0.05), whereas no such difference was detected at 6 months following the surgery (P > 0.05). Thus, compared to the MA method, the KA procedure provided pain relief and improved active motion range within 6 weeks after the surgery in patients undergoing TKA. Further, the KOOS JR exhibited significant increases at 6 weeks, 6 months, and 1 year while the FJS-12 Knee demonstrated a significant increase at 1 year after the KA TKA procedure. Conclusion Therefore, our study results suggest that the KA approach can be considered in patients using generic instruments with varus alignment of the knee, particularly those with mCPAK type I and IV varus knees, to help improve patient satisfaction.